2010
DOI: 10.4028/www.scientific.net/amr.160-162.1582
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure in Pressureless-Sintered Iron-Containing Hydroxyapatite/Titanium Composites

Abstract: Pure hydroxyapatite (HA) is brittle and it cannot be directly used for the load-bearing biomedical applications. Aim of this paper was to present a new iron-containing hydroxyapatite/titanium composites synthesized via pressureless sintering at a relatively low temperature of 1000°C using nano-sized HA powders and Ti-33%Fe mixed powders. The microstructure and composition of the new type composites were evaluated. The results showed that the uniformly distributed reinforcing particles had a unique and favorabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…% Fe) composite consisted of HA and some new phases, such as Ti, Fe, TiFe, β-CaTiO 3, etc. [ 12 , 38 ]. The contents of β-TCP and Ca 4 O(PO 4 ) 2 (TTCP) were significantly decreased, as these second phases were not detected by XRD [ 12 , 38 ].…”
Section: Interfacial Characteristics Of Titanium Alloy/ha Compositmentioning
confidence: 99%
See 4 more Smart Citations
“…% Fe) composite consisted of HA and some new phases, such as Ti, Fe, TiFe, β-CaTiO 3, etc. [ 12 , 38 ]. The contents of β-TCP and Ca 4 O(PO 4 ) 2 (TTCP) were significantly decreased, as these second phases were not detected by XRD [ 12 , 38 ].…”
Section: Interfacial Characteristics Of Titanium Alloy/ha Compositmentioning
confidence: 99%
“…[ 12 , 38 ]. The contents of β-TCP and Ca 4 O(PO 4 ) 2 (TTCP) were significantly decreased, as these second phases were not detected by XRD [ 12 , 38 ]. This showed that the addition of Iron can inhibit decomposition of HA and chemical reactions with Ti, which are related to faster diffusion rate of Iron element in Titanium at 836 °C [ 12 , 38 ].…”
Section: Interfacial Characteristics Of Titanium Alloy/ha Compositmentioning
confidence: 99%
See 3 more Smart Citations